Assessment of CDM Capacity Building Activities in Cambodia, Lao PDR and Vietnam: Lessons Learned - Dang Thi Hanh (Hamburg Institute of International Economics (HWWA), 2006)
Since the adoption of the United Nations Framework Convention on Climate Change (UNFCCC), in Rio de Janeiro, Brazil, in 1992, developing countries have continuously emphasized that assistance and capacity building are essential for them to implement the Convention effectively. The entry into force of the Kyoto Protocol of the UNFCCC in February 2005 has increased interests and activities in the Clean Development Mechanism (CDM) in developing countries and made the need for capacity building in these countries even more urgent. So far ASEAN region has been targeted by a high number of capacity building programmes. This is due to the fact that the countries offer a high CDM potential and are generally perceived to have a relatively high education level, meaning that initial capacity building efforts would readily be disseminated. Cambodia, Lao PDR and Vietnam are the three low-income countries (LICs) in this region. Among the three countries, Vietnam takes a lead in attracting donors for financial assistance and capacity building projects until now. As a least developed country (LDC), Cambodia is deemed quite successful in being involved in several regional capacity building programmes. Lao PDR lags far behind these two countries with regard to general CDM activities and capacity building particularly. This study reviews the past and on-going activities in order to assess how far these activities have contributed to addressing the capacity needs of Cambodia, Lao PDR and Vietnam in promoting CDM activities in these countries. Through the lessons and experience learned from the three countries, we endeavor to provide recommendations for future capacity building to meet the CDM capacity building needs not only in these countries but also for other host countries in general.
Keywords: Q58; Q54; 330; CDM; ASEAN; institutions